Couple relationship quality scale in the Covid-19 Context: Escala de Calidad de Relación de Pareja en el contexto COVID-19 - Arteta-Sandoval, Gissel (2022)
Introduction: The pandemic caused by COVID-19 has affected people's way of life, and particularly, couple relationships. The main of this study was to evaluate the psychometric properties of the Couple Relationship Quality Scale (CRP-ASO) within the context of the lockdown due to COVID-19, in Peru. Methods: The CRP-ASO scale was applied to 499 adults (60 % women; Mage = 41.54 years, Sage = 13.48). The internal structure of the instrument was evaluated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability was also estimated by calculating Cronbach's alpha (α) and McDonald's omega (ꞷ). Results: The results indicated a four factors structure: consensus, complicity-intimacy, satisfaction in the relationship and stability in the relationship, with high indicators of internal consistency. Conclusion: It is concluded that the instrument has satisfactory psychometric properties and can be used in similar samples.